232k views
5 votes
Y=4x +5 y=x -4 a (3, 17) b (-3, -7) c (-3, 7) d (3, 7)

User Alfamale
by
4.7k points

1 Answer

1 vote

Answer:

(-3, -7)

Explanation:

y = 4x + 5

y = x - 4

add 4 to both sides of the second equation to get y + 4 = x

plug that back into the equation to get y = 4(y + 4) +5

distribute to get y = 4y + 16 + 5

combine like terms y = 4y + 21

subtract 4y on both sides to get -3y = 21

divide both sides by -3 to get y = -7

plug -7 into the second equation to get -7 = x - 4

add 4 on both sides to get -3 = x

therefore (-3, -7)

User Yname
by
4.9k points